2019
DOI: 10.1525/abt.2019.81.7.513
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Writing Assignments on Socioscientific Issues for Large-Enrollment Introductory Cell Biology Courses

Abstract: Much evidence supports the role of writing-to-learn (WTL) assignments in improving student learning and argumentation skills. However, designing effective assignments can be challenging for instructors. We describe a process for modifying WTL assignments that were originally developed for small undergraduate biology classes (24 students) for use in large introductory cell biology courses (>80 students). Students explore a socioscientific issue (cancer treatment) intended to engage them. Students learn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A WTL field test in an introductory biology course at a public liberal arts university, based on protocols outlined in a related study ( 9 ), demonstrated their effectiveness on student performance. Three-way ANOVA results showed higher exam score improvements in the WTL semester than in the non-WTL semester ( Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A WTL field test in an introductory biology course at a public liberal arts university, based on protocols outlined in a related study ( 9 ), demonstrated their effectiveness on student performance. Three-way ANOVA results showed higher exam score improvements in the WTL semester than in the non-WTL semester ( Fig.…”
Section: Discussionmentioning
confidence: 94%
“…An outline of a cancer biology example of WTL modules is detailed in reference ( 9 ). These WTL modules contain basic components, involve an instructional team, and incorporate inclusive learning pedagogies ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WTL assignments are not routinely used in introductory foundational biology courses (3,11,12) because write-to-communicate (WTC) assignments (i.e., lab reports, exams, presentations) tend to predominate. WTC assignments often have the goal of assessing rather than explicitly facilitating understanding (13,14).…”
Section: Introduction "The First Draft Is Just You Telling Yourself T...mentioning
confidence: 99%